B3 Waste Management and Health Workers Complaint In. Inka (Persero) Madiun City - Tentrami Hayuning Ichtiakhiri; Sudarmaji Sudarmaji (JURNAL KESEHATAN LINGKUNGAN, 2015)
Abstract: Disposal  of industrial products containing chemical compounds especially harmful and toxic material negative impact  on the environment and human  health. PT. INKA (Persero)  is a company engaged in manufacturing and railway services generating B3 waste  from the production process.. B3 waste  is used oil/oil cooler  scars, B3 cans  (cans  of paint, thinner, drums), used batteries,  sand  ex. blasting,  dust ex. blasting,  plasma  crust, former rags, waste  fiber glass.  B3 waste containing various heavy  metals  such as Pb, Cu, Hg, and Fe. This can be avoided by doing  the B3 waste  management in industry.  The  purpose of this research is describing the  implementation of B3 waste  management and  perceived health  complaints of workers.  This research is a descriptive cross-sectional design. The sample of respondents was taken by total sampling with a sample size  of 10 workers  B3 waste management. The research variables  are B3 waste management (sorting, storage, collection, transportation, utilization, processing, stockpiling) and health complaints. The results  showed that PT. INKA (Persero)  has  not qualified  in terms  of B3 waste  management such as sorting  and storage. Health complaints are often perceived by employees is a headache and skin irritation. In this research required the  supervision of B3 waste  management in PT. INKA (Persero)  as well as increased awareness of workers  to wear protective equipment to manage waste.Keywords: B3 Waste Management, Health Complaints